Analysis of the Influence of Learning Strategies on the Academic Achievement of Gen-Z Students with Data Visualization Using Matplotlib in Python - Salsabila, Yovi Naila; Lutfansa, Nabila Aulia; Fadiyah, Fitri Nur; Qurotaani, Nazwa Nurul; Safira, Dessi Adelia; Yusuf, Mohamad (Journal Collabits, 2025)
This research examines the influence of learning strategies on the Grade Point Average (GPA) of Generation Z (Gen- Z) students. The background of this research is to understand how the learning strategies used by Gen-Z students affect their GPA. The research aims to analyze the influence of various learning strategies, identify the most effective ones, and demonstrate the use of the Matplotlib library in Python for data visualization. This research is quantitative in nature using statistical methods to evaluate the results. Data was collected through a questionnaire distributed to students, including the frequency of using learning strategies such as reading books, watching YouTube tutorials, doing practice questions, taking private lessons/online tutoring, and participation in training/seminars/workshops. Data analysis was carried out using Python and the Matplotlib library to visualize the data and provide a clear picture of the effectiveness of the learning strategy implemented. The research results show that active and technology- integrated learning strategies have a significant influence on increasing the academic achievement of Gen-Z students. Specifically, strategies such as watching YouTube tutorials and doing practice questions had a positive correlation with improving students' GPAs. These findings indicate the importance of adapting learning methods that suit the characteristics and learning preferences of Gen-Z students.